Prominent Reduction in Pyramidal Neurons Density in the Orbitofrontal Cortex of Elderly Depressed Patients - Rajkowska, Grazyna; Miguel-Hidalgo, Jose Javier; Dubey, Priti; Stockmeier, Craig A.; Krishnan, K. Ranga Rama (Biological psychiatry (1969), 2005)
Elderly depressed patients have more vascular hyperintensities in frontal white matter and basal ganglia than elderly control subjects. Cell pathology that might be related to increased vascular hyperintensities has not been examined. Postmortem samples from the orbitofrontal cortex (ORB) were collected in 15 elderly subjects with major depressive disorder (MDD) and 11 age-matched control subjects. Cell packing density of neurons and glia, density of pyramidal and nonpyramidal neurons, and cortical and laminar width were measured. The overall (layers I–VI) packing density of ORB neurons with pyramidal morphology was markedly decreased in MDD (by 30%) as compared with control subjects. Further laminar analysis of pyramidal neurons density revealed significant reductions in layers IIIc and V in MDD. In contrast, in MDD the density of nonpyramidal neurons and glia and cortical and laminar width were comparable to control values. In elderly subjects with depression, the density of pyramidal neurons in the ORB was particularly low in cortical layers V and III, the origin of prefronto-striatal and prefronto-cortical and prefronto-amygdalar projections. Degeneration of neurons furnishing these projections might be related to the white matter hyperintensities previously observed. Neuronal pathology seems to be more severe in elderly than in younger subjects with MDD.